Weight Loss Outcomes Among Early High Responders to Exenatide Treatment: A Randomized, Placebo Controlled Study in Overweight and Obese Women - Rodgers, Megan; Migdal, Alexandra L.; Rodríguez, Tahereh Ghorbani; Chen, Zsu-Zsu; Nath, Anjali K.; Gerszten, Robert E.; Kasid, Natasha; Toschi, Elena; Tripaldi, Juliet; Heineman, Brent; Phan, Minh; Ngo, Long; et al. (Frontiers in Endocrinology, 2021)
Objective: As there is significant heterogeneity in the weight loss response to pharmacotherapy, one of the most important clinical questions in obesity medicine is how to predict an individual’s response to pharmacotherapy. The present study examines patterns of weight loss among overweight and obese women who demonstrated early robust response to twice daily exenatide treatment compared to those treated with a hypocaloric diet and matched placebo. Methods: We randomized 182 women (BMI 25-48 kg/m2) to treatment with exenatide or hypocaloric diet with matched placebo injections. Our primary outcome was change in body weight. Women who demonstrated ≥ 5% weight loss at 12 weeks were characterized as high responders and those who lost > 10% of body weight were classified as super responders. An exploratory metabolomic analysis was also performed. Results: We observed individual variability in weight loss with both exenatide and hypocaloric diet plus placebo injections. There was no significant difference in the percentage of subjects who achieved > 5% weight loss (56% of those treated with exenatide, 76% of those treated with diet) or > 10% weight loss (43% exenatide, 55% diet). Both treatment groups also demonstrated similar peak weight loss during the study period. We observed lower cysteine concentrations in the exenatide responder group and a trend toward higher levels of serotonin, aminoisobutyric acid, anandamide, and sarcosine in the exenatide super responder group. Conclusion: In a population of early high responders, longer term weight loss with exenatide treatment is similar to that achieved with a hypocaloric diet.